Why Don't Present-Biased Agents Make Commitments? - Laibson, David (American Economic Review, 2015)
Present-biased preferences engender a demand for commitment. Commitment is a problematic prediction, since we see so little of it. I quantitatively explore the reasons for the “missing” commitment. Extending the procrastination model in Carroll et al. (2009), I show how equilibrium commitment is related to (i) the standard deviation of the opportunity cost of time, (ii) the cost of delay, (iii) the degree of partial naivete, and (iv) the direct cost of commitment. The calibrated model demonstrates that the perceived benefits of commitment are often overwhelmed by the costs of commitment. Demand for commitment is a special case rather than the general case.